Direct and Indirect Speech Acts in Job Advertising - Šindlerová, Dominika (Univerzita Pardubice, 2017)
This thesis is devoted to the analysis of direct and indirect speech acts and their illocutionary force in job advertising. The theoretical part describes job advertising, its forms, content and persuasive function. Speech acts theory developed by J. Austin is introduced, their direct and indirect forms are distinguished and the illocutionary force of sentences is explained. The classification of speech acts developed by Searle is explained and functions as a basis for the analysis. The analytical part examines the occurrence of direct and indirect speech acts, their form and function, in provided job advertisements.
Direct and Indirect Speech Acts in Job Advertisements
Přímé a nepřímé řečové akty v inzerci pracovních příležitostí
Keywords: řečové akty; ilokuční akty; ilokuční síla; inzerce pracovních příležitostí; přímost; nepřímost; přesvědčovací funkce; zdvořilost; speech acts; illocutionary acts; illocutionary force; job advertising; directness; indirectness; persuasive function; politeness